Naltrexone and Bupropion Combination Treatment for Smoking Cessation and Weight Loss in Patients With Schizophrenia - Lyu, Xuechan; Du, Jiang; Zhan, Guilai; Wu, Yujie; Su, Hang; Zhu, Youwei; Jarskog, Fredrik; Zhao, Min; Fan, Xiaoduo (Frontiers in Pharmacology, 2018)
Objective: The rates of obesity and cigarette smoking are much higher in patients with schizophrenia compared to the general population. This study was to examine whether naltrexone and bupropion combination treatment can help weight loss and smoking cessation in patients with schizophrenia. Methods: Obese male schizophrenia patients with current cigarette smoking were randomized to receive adjunctive naltrexone (25mg/day) and bupropion (300mg/day) combination or placebo for 24 weeks. Twenty-two patients were enrolled in the study, and 21 patients completed the study (11 in the treatment group, and 10 in the placebo group). Body weight, body mass index (BMI), fasting lipids, smoking urge, expired carbon monoxide (CO) level and cigarettes smoked per week were measured at baseline and week 24. Results: There was no significant difference between two groups in changes in weight, BMI, fasting lipids or cigarette smoking measures (p’s > 0.05) Conclusion: Naltrexone and bupropion combination treatment didn’t show weight loss or smoking cessation effect in patients with schizophrenia in this pilot study. Implications for future studies were discussed.